2020
DOI: 10.15316/sjafs.2020.217
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield and Characteristics in a Half-Diallel Pumpkin Population

Abstract: In addition to fresh and roasted pumpkin seeds used in human nutrition, they are used as an additive to bread, salami, sausage, mayonnaise and many food products because of their high protein content. The most common problem encountered in the cultivation of confectionary pumpkin is the lack of varieties with good seed yield and quality in the market. In this study, it was aimed to reveal the promising hybrids with superior characteristics by determining the yield and seed characteristics of the 13 pumpkin inb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Kayak et al (2020) reported that the G39 genotype, located in the positive region of both components, showed superior characteristics in terms of yield and fruit quality and could be a promising cultivar candidate in their melon study. Similarly, Seymen (2020) reported that the hybrid cultivar candidates 31x34, 23x28, 13x23, 38x40, 29x37, 30x31 and 23x29 and 40x29, located in the positive region of both components, are promising. In conclusion, with the study, some yield and quality characteristics of 85 hybrid melon cultivar candidates were revealed in Konya ecological conditions.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Kayak et al (2020) reported that the G39 genotype, located in the positive region of both components, showed superior characteristics in terms of yield and fruit quality and could be a promising cultivar candidate in their melon study. Similarly, Seymen (2020) reported that the hybrid cultivar candidates 31x34, 23x28, 13x23, 38x40, 29x37, 30x31 and 23x29 and 40x29, located in the positive region of both components, are promising. In conclusion, with the study, some yield and quality characteristics of 85 hybrid melon cultivar candidates were revealed in Konya ecological conditions.…”
Section: Resultsmentioning
confidence: 86%
“…In the study, F1 melon cultivar candidates were tried to be defined with the loading plot graph drawn from the first four components because of PCA made from yield and fruit parameters obtained from 85 melon cultivar candidates (Figure 1). Similar methods have been applied in different studies to identify genotypes in a large genetic pool (Seymen et al, 2019;Kayak et al, 2020;Seymen, 2020). When the figure is examined, the positive region of PC1 was the region explained in terms of fruit rind color.…”
Section: Resultsmentioning
confidence: 94%